Constituição e tráfico de drogas: a face oculta da repressão na exceção permanente brasileira - Duarte, Daniel Nascimento (2014)
It is intended to revolve the issue of drug enforcement in Brazil from the theory of the permanent state of exception worked by the italian theorist Giorgio Agamben. For that, after due theoretical allocation, which pervaded by the influences of Carl Schmitt (1888-1985) and Walter Benjamin (1892-1940), the characteristics and vectors of a contemporary theory for the state of exception are traced in order to identify it as the paradigm of governmental contemporaneity. Subsequently, lies in the brazilian background of the war on drugs, a privileged scope of paradigmatic absorption and confirmation of the of contemporary logic of permanent exception. Highlighting the constant increase of the military justifications guided by emergency, order and security speeches, and with attention to the increasingly harmful development of the penal state, we sought to, through the critical criminological influence, identify the biopolitical vectors of the state of exception on Brazil's criminal policy of war on drugs. For the last, we attempted to identify in the traffic repressive constitutional text also a paradigmatic absorption of the war on drugs in order to outline a maintenance of the fighting logic in the repressive context and demonstrate, from the repressive constitutional text, strengthening the state of exception's paradigm standing in the Brazilian land.